A facile synthesis of novel indole derivatives as potential antitubercular agents. Issue 6 (1st November 2017) - Khan, Gulzar A.; War, Javeed A.; Kumar, Arun; Sheikh, Imtiyaz A.; Saxena, Aarti; Das, Ratnesh
Abstract: A novel series of 5, 5-dimethyl-11-phenyl-4b, 5, 5a, 10, 10a, 11, 11a, 12-octahydro-10, 11, 12-triaza-indeno[2, 1-b]fluorenes 3a–3l were prepared by reacting oxindole, aryl amines and acetone using dibutylamine as an organocatalyst via simultaneous Knoevenagel and Michael-type reactions. This preparation is environmentally benign, highly compatible and conveniently carried out in ethanol under mild conditions. The structures of the new compounds were determined by spectroscopic techniques, including IR, 1 H NMR, 13 C NMR and LCHRMS. Docking studies against an enoyl acyl carrier protein reductase predicted that the compounds possessed high binding affinity towards target molecules. The compound 3k (MIC, 40 μg/mL) showed comparable activity with Isoniazid at the same concentrations against MT H37 Rv.